Analysis of molecular isotopic structures at high precision and accuracy by Orbitrap mass spectrometry - Eiler, J.; Cesar, J.; Chimiak, L.; Dallas, B.; Grice, Kliti; Griep-Raming, J.; Juchelka, D.; Kitchen, N.; Lloyd, M.; Makarov, A.; Robins, R.; Schwieters, J. (Wiley InterScience, 2017)
© 2017 Elsevier B.V. Several technologies are being developed to examine the intramolecular isotopic structures of molecules (i.e., site-specific and multiple substitution), but limitations in sample size and type or (for mass spectrometry) resolution have so far prevented the creation of a general technique. We have now demonstrated the capacity for precise and accurate study of molecular isotopic contents and structures by Fourier transform mass spectrometry, using instruments containing a Thermo Scientific™ Orbitrap™ mass analyzer, here the Thermo Scientific Q Exactive GC™ and Q Exactive HF™ instruments. Orbitrap mass analyzers achieve mass resolutions in the range ~250,000-1. M (FWHM) in the mass range of greatest interest to studies of molecular isotopic structure, 50-200. amu. This allows for resolution of many nearly isobaric interferences for compounds containing H, C, N, O and/or S. In this paper we show that internal and external experimental reproducibilities of isotope ratio analyses using the Orbitrap analysis can conform to shot-noise lim its down to levels of tenths of per mil (1SE), with similar accuracy when standardized to reference materials. Precision reaches ±0.015‰ for exceptionally long integrations. Such measurements do not call for modifications to the ion optics of the Q Exactive instruments, but do require specially designed sample introduction devices to permit sample/standard comparison and long integration times. The sensitivity of the Q Exactive instruments permit analysis of sub-nanomolar samples and quantification of multiply-substituted species. Site-specific capabilities arise from the fact that mass spectra of molecular analytes commonly contain diverse fragment ion species, each of which samples a specific sub-set of molecular sites.